EFFECT OF PROBIOTIC FERMENTATION ON THE INVITRO DIGESTIBILITY OF STARCH AND PROTEIN OF BANANA BASED FOOD MIXTURES - Sharon, C. L. (IJRDO-Journal of Applied Science, 2015)
The consumers over whelming interest for functional foods, including probiotics have resulted in attempts to develop fourteen probiotic food mixtures containing banana flour, green gram flour, soya flour, tomato, mango and papaya. 25 g of each mixture was mixed with 150 ml of distilled water and adjusted the pH to 4.5 and autoclaved at 121° C (1.5 kg/cm2) for 15 mts. After cooling this was inoculated with 300µl (119×106 cfu/ml) liquid culture of L.acidophilus (24 hour old culture) and incubated at 37° C for 24 hours. After fermentation it was freeze dried and the samples were analysed for thier organoleptic qualities, viability of L acidophilus, invitro starch (IVSD) and invitro protein (IVPD) digestibility. The unfermented samples served as control. The IVSD and IVPD varied between 78.57% to 83.60 % and 85.14% to 86.21% respectively in fermented food mixtures. The viability of L. acidophilis varied from 136 to 292 x 10 7cfu/g